Friction controls even submerged granular flows. Issue 41 (9th October 2017) - Koivisto, Juha; Korhonen, Marko; Alava, Mikko; Ortiz, Carlos P.; Durian, Douglas J.; Puisto, Antti
Abstract : A recently discovered counterintuitive surge in granular hopper flows is successfully modeled using discrete elements coupled with computational fluid mechanics. Abstract : We investigate the coupling between the interstitial medium and granular particles by studying the hopper flow of dry and submerged systems experimentally and numerically. In accordance with earlier studies, we find that the dry hopper empties at a constant rate. However, in the submerged system we observe the surging of the flow rate. We model both systems using the discrete element method, which we couple with computational fluid dynamics in the case of a submerged hopper. We are able to match the simulations and the experiments with good accuracy by fitting the particle–particle contact friction for each system separately. Submerging the hopper changes the particle–particle contact friction from μ vacuum = 0.15 to μ sub = 0.13, while all the other simulation parameters remain the same.